2009
DOI: 10.1007/s12540-009-0733-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alloying and pressing routes in equal channel angular pressing of Cu-Fe-Cr and Cu-Fe-Cr-Ag composites

Abstract: Equal channel angular pressing (ECAP) was carried out on Cu-Fe-Cr and Cu-Fe-Cr-Ag composites at room temperature. ECAPed Cu-Fe-Cr and Cu-Fe-Cr-Ag exhibited ultrafine-grained microstructures with the shape and distribution of Fe-Cr phase were dependent on the processing routes. In route A, the initial dendrites of Fe-Cr phase were elongated along the shear direction and developed into filaments, whereas in route Bc the initial dendrites became finer by fragmentation with no pronounced change of the shape. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…wires) thick enough for the applications. The ECAP processing here has been carried out using the socalled route A [20], whereby there is no rotation of sample between successive ECAP passes, since other routes can lead to ribbon fragmentation during processing [22]. Such fragmentation should be avoided since the presence of Fe phase as relatively long ribbons is believed to be important for achieving high strength [4][5][6]8,[11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…wires) thick enough for the applications. The ECAP processing here has been carried out using the socalled route A [20], whereby there is no rotation of sample between successive ECAP passes, since other routes can lead to ribbon fragmentation during processing [22]. Such fragmentation should be avoided since the presence of Fe phase as relatively long ribbons is believed to be important for achieving high strength [4][5][6]8,[11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The most likely explanation for the observed inefficiency of the ECAP + rolling processing for microstructural refinement is the slow build up of substructure during ECAP by route A. A number of previous studies have shown that altering strain paths, for example by using route B or C for ECAP [20] or using rolling or drawing methods, is more effective at strengthening by microstructural refinement than using route A for ECAP [22,[34][35][36][37][38][39]. It seems likely that the preliminary ECAP stage sets up a relatively coarse deformation substructure, based on a given set of operating slip systems, and there will be a change of suitable slip systems when further plastic strain is imposed by rolling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations